A life in shadow : Aimé Bonpland in southern South America, 1817-1858 - Bell, Stephen, 1956- (Stanford University Press, 2010)
French naturalist and medical doctor Aimé Bonpland (1773-1858) was one of the most important scientific explorers of South America in the early nineteenth century. From 1799 to 1804, he worked alongside Alexander von Humboldt as the latter carried out his celebrated research in northern South America, but he later returned to conduct his own research farther south. This book accounts for the entire span of Bonpland's remarkable and diverse career in South America - in Argentina, Paraguay (where he was imprisoned for nearly a decade), Uruguay, and southernmost Brazil - based on extensive archival material.